The Center Holds Quite Well: An Ethnographic Study of Social Structure and Control in Jehovah’s Witness Religious Organization - Trahan, Adam (International Journal of Criminology and Sociology, 2013)
Religion has long occupied a singularly prominent position among the various institutions of social control. Evidence suggests, however, that the American religious milieu has changed in recent decades. Several historically fringe religions have grown in terms of power and influence while traditionally dominant religious institutions have deteriorated. One of the fastest growing religious organizations is Jehovah’s Witness. Despite its increasingly powerful role in American society, we know very little about how Jehovah’s Witness operates as a system of social control. This paper presents the findings of an ethnographic study of the mechanisms with which Jehovah’s Witness’ construct and control deviance. The results demonstrate that Jehovah’s Witness operates according to the principles of functional systems theory. Witnesses are isolated from other social systems, which are deemed evil, and those who stray are shamed and labeled. Growth is maintained through careful evangelism processes that minimize threats to the organization and socialize core values to willing participants.